Effect of the potential probiotic Vibrio proteolyticus DCF12.2 on the immune system of Solea senegalensis and protection against Photobacterium damselae subsp. piscicida and Vibrio harveyi - Medina, Alberto; García-Márquez, Jorge; Moriñigo-Gutiérrez, Miguel Ángel; Arijo-Andrade, Salvador (MDPI, 2023)
Some of the characteristics of probiotics used in aquaculture are the antagonistic activity against pathogens and the activation of the immune response. Moreover, some probiotics with common antigens to pathogens can produce antibodies that react with these pathogens. One of those potential probiotics is Vibrio proteolyticus DCF12.2, a strain with the capacity to produce antibodies in soles (Solea senegalensis) that react with Photobacterium damselae subsp. piscicida and Vibrio harveyi antigens. Therefore, the objective of the work was to determine the capacity of DCF12.2 to activate the immune response in the sole, providing protection against both pathogens. For this purpose, DCF12.2 was administered to cultured soles by intraperitoneal injection, bath, and diet. The DCF12.2 strain activated the gene expression related to the fish immune response and increased the antibody production with cross-reaction to P. damselae subsp. piscicida and V. harveyi cells. Challenges with P. damselae subsp. piscicida resulted in a 30–40% relative percent survival (RPS) through DCF12.2 treatments. After challenge with V. harveyi, only intraperitoneal treatment protected the fish (67% RPS). In conclusion, the DCF12.2 strain showed great potential to be used to prevent diseases caused by both pathogens, and indicates a way to use probiotics as live vaccines.
Keywords: Acuicultura; Probióticos; Antibody cross-reaction; Aquaculture; Fish pathogenic bacteria; Gene expression; Immune response